Tocilizumab in early progressive rheumatoid arthritis: FUNCTION, a randomised controlled trial. Issue 6 (28th October 2015) - Burmester, Gerd R; Rigby, William F; van Vollenhoven, Ronald F; Kay, Jonathan; Rubbert-Roth, Andrea; Kelman, Ariella; Dimonaco, Sophie; Mitchell, Nina
Abstract : Objectives: The efficacy of tocilizumab (TCZ), an anti-interleukin-6 receptor antibody, has not previously been evaluated in a population consisting exclusively of patients with early rheumatoid arthritis (RA). Methods: In a double-blind randomised controlled trial (FUNCTION), 1162 methotrexate (MTX)-naive patients with early progressive RA were randomly assigned (1:1:1:1) to one of four treatment groups: 4 mg/kg TCZ+MTX, 8 mg/kg TCZ+MTX, 8 mg/kg TCZ+placebo and placebo+MTX (comparator group). The primary outcome was remission according to Disease Activity Score using 28 joints (DAS28–erythrocyte sedimentation rate (ESR) <2.6) at week 24. Radiographic and physical function outcomes were also evaluated. We report results through week 52. Results: The intent-to-treat population included 1157 patients. Significantly more patients receiving 8 mg/kg TCZ+MTX and 8 mg/kg TCZ+placebo than receiving placebo+MTX achieved DAS28-ESR remission at week 24 (45% and 39% vs 15%; p<0.0001). The 8 mg/kg TCZ+MTX group also achieved significantly greater improvement in radiographic disease progression and physical function at week 52 than did patients treated with placebo+MTX (mean change from baseline in van der Heijde–modified total Sharp score, 0.08 vs 1.14 (p=0.0001); mean reduction in Health Assessment Disability Index, −0.81 vs −0.64 (p=0.0024)). In addition, the 8 mg/kg TCZ+placebo and 4 mg/kg TCZ+MTX groups demonstrated clinical efficacy that was at least as effective as MTX for these key secondary endpoints. Serious adverse events were similar among treatment groups. Adverse events resulting in premature withdrawal occurred in 20% of patients in the 8 mg/kg TCZ+MTX group. Conclusions: TCZ is effective in combination with MTX and as monotherapy for the treatment of patients with early RA. Trial registration number: ClinicalTrials.gov, number NCT01007435